2005
DOI: 10.2174/1389201054553716
|View full text |Cite
|
Sign up to set email alerts
|

Neurovestibular and Sensorimotor Studies in Space and Earth Benefits

Abstract: This review summarizes what has been learned from studies of human neurovestibular system in weightless conditions, including balance and locomotion, gaze control, vestibular-autonomic function and spatial orientation, and gives some examples of the potential Earth benefits of this research. Results show that when astronauts and cosmonauts return from space flight both the peripheral and central neural processes are physiologically and functionally altered. There are clear distinctions between the virtually im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 53 publications
(58 reference statements)
0
17
0
Order By: Relevance
“…The (right) inferior parietal lobe (BA40), the (left) anterior cingulate gyrus (BA 32) and the (left) middle temporal gyrus (BA 39) were more active in weightlessness than on Earth. These areas together with both cerebellar hemispheres have been identified as part of the vestibular system in humans47 which is altered in weightlessness14. The alpha ERD recorded in this network may reflect a challenge of an increased demand to integrate partially reduced or incongruent vestibular information while free-floating20.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The (right) inferior parietal lobe (BA40), the (left) anterior cingulate gyrus (BA 32) and the (left) middle temporal gyrus (BA 39) were more active in weightlessness than on Earth. These areas together with both cerebellar hemispheres have been identified as part of the vestibular system in humans47 which is altered in weightlessness14. The alpha ERD recorded in this network may reflect a challenge of an increased demand to integrate partially reduced or incongruent vestibular information while free-floating20.…”
Section: Discussionmentioning
confidence: 98%
“…In microgravity the multiple sensory inputs must be dynamically re-weighted in order to maintain the behavioural goals13. The central nervous system must properly adapt in order to organize the control of functions such as posture, eye-hand coordination, spatial orientation and navigation14. Astronauts’ performance remains good after a variable period of adaptation12151617.…”
mentioning
confidence: 99%
“…It particularly affects otolith function, which is an important sensor of translational motion and serves a key role in control of eye movement and posture. Studies of neuro-vestibular function both during and after spaceflight have demonstrated abnormal otolith-ocular reflexes and spatial perception both during adaptation to microgravity as well as re-adaptation after return to Earth (8). In addition to its well-established role in spatial orientation, gaze control, and neuromotor function, recent work has demonstrated the presence of vestibulo-autonomic reflexes (32, 33, 36, 56, 57, 66).…”
Section: Mechanisms Of Altered Autonomic Function In Spacementioning
confidence: 99%
“…Spaceflight may negatively affect neurovestibular and sensorimotor functions, particularly posture and locomotor control, gaze stabilization and spatial orientation. 104,105 Disturbances in neurovestibular and sensorimotor functions can result in degraded performance of operational tasks on orbit, inability to perform emergency egress, and impairments in performing normal daily activities for varying periods after landing. Absence of gravitational stimulation of the otolith organ seems to be heavily implicated in the observed neurovestibular effects.…”
Section: Neurovestibular and Sensory Motor Dysfunctionmentioning
confidence: 99%